Underpricing of Initial Public Offerings in Hot and Cold Markets: An Empirical Study on Borsa Istanbul - Ezgi Tuncay; Mehmet Karan; Eren Miski Aydin (The Central European Review of Economics and Management (CEREM), 2020)
The study aims to evaluate the initial public offering performance of Borsa Istanbul companies during the hot and cold periods. The size of the companies, industry concentration and investor optimism are considered in this respect.~ The study covers the 119 IPOs of various sizes from different industries between 2010 and 2017 just after the global financial crisis. The standard event study methodology is applied. This study has revealed the existence of post-crisis underpricing effects in Turkey. Moreover, the research shows that although low pricing is valid in hot periods, hot and cold markets do not differ significantly from each other in this context. Besides, this study finds that the low price effect exists for small firms, and this effect is more common in hot markets. On the other hand, although there is a relationship between consumer confidence index and low price, no relation with industry concentration was found.
Keywords: 330